Land, poverty and human development in Kenya - Mwangi wa Githinji (University of Massachusetts, Department of Economics, 2011)
The question of poverty has become central to the work of development economists in the last decade and a half. The 2000 World Development Report was entitled Attacking Poverty and the UN held a series of World Conferences in the 1990s, all of which addressed in some form or fashion the problem of poverty. Despite this and because of limited data there has been relatively little empirical work at the household level on determinants of poverty in Africa generally and Kenya specifically. In the few econometric studies that have been done for Kenya land has not been a significant determinant of poverty. This is a surprising result for a country where 80 per cent of the population depends on agriculture. Further the little that has been done has not incorporated the role of human development in the determination of poverty. Via an examination of a nationwide sample this paper will examine the role that land and social capital play in determining households poverty status in rural Kenya in addition to the standard theorized determinants.
Keywords: O15; Q15; 330; Poverty; Rural; Land; Kenya; Africa; Human Development